Revisão bibliográfica sobre a evolução do uso de macrobiológicos na canavicultura - Sibille, Henrique Costa (Universidade Federal de São Carlos, 2025)
Sugarcane cultivation is one of the most important agricultural activities in the history of Brazil, from the colonial period to the present day, maintaining significant economic and social relevance. Currently, the sector stands out as one of the pillars of Brazilian agribusiness. In 2023, sugarcane generated approximately R$ 111.2 billion from a cultivated area of about 9.6 million hectares. However, the use of intensive monoculture systems can lead to ecological imbalances, favoring the development of pest insect outbreaks. These organisms, in turn, have natural enemies capable of regulating their populations naturally. This review aimed to revisit the trajectory and development of biological control in sugarcane crops, with emphasis on the use of macrobiological agents and on the consolidation of species such as Cotesia flavipes and Trichogramma galloi in the management of the sugarcane borer, Diatraea saccharalis. The study sought to understand the evolution of biological control practices in Brazil by identifying historical milestones, advances, challenges, and future perspectives, reinforcing its importance as a tool for sustainability and competitiveness in Brazilian tropical agriculture.
Literature review on the evolution of the use of macrobiological agents in sugarcane cultivation
Keywords: Cana-de-açúcar; Controle biológico; Parasitoides; Diatraea saccharalis; Cotesia flavipes; Sugarcane; Biological control; Parasitoids; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE; 2. Fome Zero e Agricultura Sustentável; 12. Consumo e Produção Responsáveis